Detailed ecological associations of triatomines revealed by metabarcoding and next-generation sequencing: implications for triatomine behavior and Trypanosoma cruzi transmission cycles - Dumonteil, Eric (Sci Rep, 2018)
Trypanosoma cruzi is the agent of Chagas disease, transmitted by hematophagous triatomine vectors. Establishing transmission cycles is key to understand the epidemiology of the disease, but integrative assessments of ecological interactions shaping parasite transmission are still limited. Current approaches also lack sensitivity to assess the full extent of this ecological diversity. Here we developed a metabarcoding approach based on next-generation sequencing to identify triatomine gut microbiome, vertebrate feeding hosts, and parasite diversity and their potential interactions. We detected a dynamic microbiome in Triatoma dimidiata, including 23 bacterial orders, which differed according to blood sources. Fourteen vertebrate species served as blood sources, corresponding to domestic, synantropic and sylvatic species, although four (human, dog, cow and mice) accounted for over 50% of blood sources. Importantly, bugs fed on multiple hosts, with up to 11 hosts identified per bug, indicating very frequent host-switching. A high clonal diversity of T. cruzi was detected, with up to 20 haplotypes per bug. This analysis provided much greater sensitivity to detect multiple blood meals and multiclonal infections with T. cruzi, which should be taken into account to develop transmission networks, and characterize the risk for human infection, eventually leading to a better control of disease transmission.